PENERAPAN MODEL PEMBELAJARAN SOLE UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS VI DALAM PEMBELAJARAN IPS MATERI NEGARA ANGGOTA ASEAN - Ananda Khairani, - (2023)
Low critical thinking skills go hand in hand with low student learning results. Teachers still aren't using instructional strategies that promote critical thinking when students are in their classes. The SOLE (Self Organized Learning Environments) learning paradigm, according to Fatwatus (2019), was created to inspire students to work hard and study in order to respond to inquiries that pique interest in learning how to utilize the internet. The SOLE learning model is guided by curiosity, self-exploration, knowledge sharing, and improvisation. This study employs qualitative research techniques based on Classroom Action Research (CAR). Sixteen children from SDN Sayabulu's sixth grade served as participants for this experiment. Researchers relied on methods like testing and documenting what they saw in the wild to compile their findings. The findings showed that in cycle I, 46.25 percent of students used SOLE, whereas in cycle II, that number grew to 81.25 percent of students. In the meanwhile, students' average performance on critical thinking examinations improved from 49.68 in the pre-cycle to 61.87 in cycle I, and then to 79.86 in cycle II, putting them firmly in the excellent range. Based on their findings, the authors of this paper advocate for implementing the SOLE model in sixth grade social studies classrooms.